STUDY ON TYPES OF SOIL DEGRADATION CAUSED BY FOREST EXPLOITATION - FLĂMÎND, Lazăr; MICLE, Valer; BOROŞ, Melania–Nicoleta (Studia Universitatis Babeș-Bolyai Ambientum, 2016)
Sustainable management and development of forest sector should become an essential element in the strategy of prevention of the degradation of the land of each state. The forests play an important role in debts settlement of water courses, in ensuring the water quality, in maintaining land stability including the erosion control, landslides or avalanches. Forest exploitation represents a main source on degradation on the soil, having a major impact on the environment. Accelerated erosion caused by forest exploitation and soil degradation has become the main factor which limits the sustainable use of the soil. Through irrational forest exploitation, the nature of damage that occurs is ecological, social and economic. Forests are sources of other goods and services for society, such as processed wood and non-wood products, space of recreation, landscaping, etc. The large number of sites affected as a result of the forest exploitation, emphasizes massive environmental risks and their existence without urgent action has a negative impact on human health and the environment.